2017
DOI: 10.24960/jli.v7i1.2691.29-39
|View full text |Cite
|
Sign up to set email alerts
|

Pengolahan Limbah Cair Rumah Sakit secara Sonochemical

Abstract: Hospital as a service provider has an important role in human life, especially for people who are experiencing physical and mental disorders. Various types of diseases and therapies performed in hospitals has made it as one of the producers of hazardous and infectious waste that requires special handling and processing so as not to pollute the water, soil, and air environment. Hospital wastewater treatment was conducted to determine the ability of sonochemical method to reduce level of Chemical Oxygen Demand (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Coefficient Variation (CV) is another metric that may be used to determine whether or not a model is significant by comparing the estimated standard error to the average value of the experimental model. The CV value should not be greater than 10% in order for the model to be considered significant [36]. The fewer values of CV value, correlates with the measurement precision of the analysis technique.…”
Section: Optimization Using Rsm-ccd Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Coefficient Variation (CV) is another metric that may be used to determine whether or not a model is significant by comparing the estimated standard error to the average value of the experimental model. The CV value should not be greater than 10% in order for the model to be considered significant [36]. The fewer values of CV value, correlates with the measurement precision of the analysis technique.…”
Section: Optimization Using Rsm-ccd Designmentioning
confidence: 99%
“…The insignificant lack of fit value indicates that the compiled model is good enough because the compiled model must be fit. Based on the data acquired in the ANOVA test, a Fvalue 4.19 and p-value 0.1001 was produced, which indicated that the lack of fit was not significant relative to pure errors [36]. So, it can be concluded that this model can be used to describe response data for Cr (VI) removal efficiency, and the model used is suitable for predicting the conditions of the coagulation-flocculation process that result in optimum Cr (VI) removal efficiency.…”
Section: Optimization Using Rsm-ccd Designmentioning
confidence: 99%
“…Hospital discharges increase proportionally to the need for health services every year continuously. WWTP has been applied to hospitals in Aceh, yet not all of them function effectively or fulfill all standards (Kusuma et al 2017). Effective wastewater treatment is necessary to prevent the spread of bacteria from hospital wastewater to the environment.…”
Section: Introductionmentioning
confidence: 99%